Surgical Treatment for Thoracic Myelopathy Due to Simultaneous Ossification of the Posterior Longitudinal Ligament and Ligamentum Flavum at the Same Level. Issue 8 (October 2016) - Onishi, Eijiro; Sano, Hirokazu; Matsushita, Mutsumi
Abstract : Study Design: Retrospective review. Objective: The aim of this study was to assess the clinical outcomes of surgery in patients with simultaneous ossification of the posterior longitudinal ligament (OPLL) and ossification of the ligamentum flavum (OLF) at the same thoracic spine level and identify the risk factors for poor outcomes. Summary of Background Data: OPLL complicated with OLF in the thoracic spine is a rare condition. The optimal treatment option for thoracic myelopathy due to OPLL and OLF remains controversial, and high risk of postoperative paralysis remains a major complication. Methods: We conducted a retrospective review of clinical and radiographic records of 15 patients who underwent surgery for simultaneous OPLL and OLF at the same level. Results: Simultaneous OPLL and OLF occurred in the upper thoracic spine in 3 patients (20%), mid-thoracic spine in 10 patients (67%), and lower thoracic spine in 2 patients (13%). Six, 4, 2, and 3 patients underwent posterior decompression, posterior decompression and fusion, posterior decompression and circumferential decompression through a posterior approach, and circumferential decompression and posterior fusion, respectively. The mean Japanese Orthopaedic Association score before surgery and at the final follow-up was 5.7±1.9 and 7.0±2.1 points, respectively, yielding a mean recovery rate of 16.5%. However, no significant difference was observed between preoperative and postoperative Japanese Orthopaedic Association scores. Two patients with mid-thoracic lesions reported postoperative lower extremity weakness. Mid-thoracic lesions and considerable blood loss were risk factors for poor surgical outcome. Conclusions: Simultaneous OPLL and OLF in the mid-thoracic spine was observed in two thirds of the patients. We suggest that simultaneous OPLL and OLF in this area has a relatively poor recovery and may be very challenging and risky to treat, regardless of the surgical method selected, and recommend early surgery for OPLL and OLF in the mid-thoracic spine.